Kepemimpinan di Era Digital dan Implementasinya di Lembaga Pendidikan - Raodatul Jannah; Ade Muhamad Rosyidin; Tati Nurmala; Nining Yuningsih; Effry Yenny (Syntax Corporation Indonesia, 2023)
A leader without anyone else willing to follow, is not a leader, but only someone who walks alone without anyone to follow or even accompany. A leader has a future orientation, not a short-term orientation that can only be enjoyed temporarily, but thinking about ideal conditions or circumstances, such as what should be achieved together in the future. A leader who cares for others and not only thinks about his own interests is willing to empower others. Leaders who keep abreast of technological developments must have skills in influencing, encouraging, guiding, directing, and mobilizing other people who have something to do with the implementation and development of education and teaching in the digital era. The method in this study is to use a descriptive qualitative approach. Scientific Literature Study. The data were collected from various scientific journals, analyzed and synthesized to then draw conclusions. Qualitative research is collecting data from various sources that are relevant to the focus of the problem set, describing, reducing and selecting so that conclusions can be drawn and presented informatively. Literature study method is a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. This study aims to make existing knowledge related to the topics to be studied to find empty space for researchers to do.